Evapotranspiration of upland paddy - MASKE , S. J.; RATHORE, L. S. (MAUSAM, 1990)
The cumulative evapotranspiration for early maturing varieties (duration 85-116 days) of upland paddy was found to be in the range of 430, 5 to 598.9 mm. The average daily evapotranspiration over the crop period was found to be 4,67 to 6.07 mm/day depending upon varietal type and location. The booting, heading and flowering stages as critical stages as these exhibit peak period of water consumption. The water use efficiency of the crop varied from 2.31 to 8, 34 kg/ha/mm.